CENOZOIC VOLCANISM OF THE KORYAK HIGHLAND SOUTHEAST: PETROGENESIS OF ROCKS AND SETTINGS OF THEIR FORMATION - Fedorov P.I.; Koloskov A.V. (My University, 2001)
Within Cenozoic volcanogenic formations in the Koryak Highland southeast there have been recognized three complexes related to the extension zones on the continental margin: Danian-Paleocene, Miocene and Early Quaternary. The Danian-Paleocene and Miocene complexes are represented by tholeiitic series rocks, the Early Quaternary complex comprises rocks of alkali olivine-basaltic and basanitic series. Peculiarities of petrogenic and rare element distribution have been considered allowing to make a conclusion on the formation of volcanic rocks from heterogeneous magma-generating sources under various geodynamic regimes.
Keywords: Cenozoic; Koryak highland; volcanism; Cenozoic; Кайнозой